Changes in youth public psychiatric service utilization during the COVID-19 pandemic in Italy: an observational study - Antonazzo, Ippazio Cosimo; Fornari, Carla; Zamparini, Manuel; Crotti, Giacomo; Zucchi, Alberto; Ferrara, Pietro; Piraino, Alexandra Maria; Cortesi, Paolo Angelo; Losa, Lorenzo; Mazzaglia, Giampiero; Mantovani, Lorenzo Giovanni (Frontiers in Pharmacology, 2026)
IntroductionSocial restrictions due to the COVID-19 pandemic have impacted the lives of children and adolescents worldwide. In this study, we aim to evaluate the impact of lockdown periods implemented in Italy during the SARS-CoV-2 waves on the mental health of minors.MethodsA population-based study using Italian healthcare administrative databases was conducted. Weekly time series of emergency department (ED) accesses/hospitalizations for psychiatric disorders, along with the incidence of antidepressant/antipsychotic (AD/AP) drug users, were defined from 1 January 2017 to 31 December 2022. An interrupted time-series analysis was used to assess the effect of lockdowns on the observed outcomes. The results were reported as incidence rate ratios (IRRs) with their respective 95% confidence intervals (95% CIs).ResultsThe first lockdown was associated with an abrupt reduction in both the incidence of AD/AP use (IRR = 0.49; 95% CI = 0.34–0.72) and ED accesses/hospitalizations for psychiatric disorders (IRR = 0.15; 95% CI = 0.10–0.23) compared to the pre-pandemic period. The incidence of AD/AP medication users showed a marked increase in both the post-first lockdown period (IRR = 2.48; 95% CI = 1.71–3.59) and the post-second lockdown period (IRR = 1.26; 95% CI = 1.07–1.48). ED accesses/hospitalizations showed a marked increase in the post-first lockdown period (IRR = 1.90; 95% CI = 1.40–2.59).ConclusionThe different lockdowns implemented during the COVID-19 outbreaks markedly affected the mental health of minors, as suggested by the increased use of AD/AP medications, which can be considered a proxy of diseases. The increased use of AD/AP medications in the observed period calls for interventions to improve the mental health of the population. These findings highlight the need to ensure effective public health interventions to be prepared for future crises.